Use of Plasmapheresis in Managing the Diagnostic Dilemma of Symptomatic Hypertriglyceridemia - Nigel Gordon Maher; Hariharan Ramaswamykanive (Case Reports in Gastrointestinal Medicine)
We present a case study of a 29-year-old male who presented with abdominal pain typical for pancreatitis. Detailed history and investigations revealed that the cause of abdominal pain was secondary to the raised triglyceride levels. It was difficult to distinguish whether he had hypertriglyceridemia-induced abdominal pain or acute pancreatitis, given that he had only a mildly raised lipase and a normal contrast computed tomography scan of the pancreas. The abdominal pain resolved with the fall in the triglyceride levels following plasmapheresis. Plasmapheresis is an underevaluated modality of the treatment of hypertriglyceridemia due to its cost and availability.